2017
DOI: 10.1021/acs.chemmater.7b03271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Electrochemical Properties of LiFeV2O7

Abstract: The structure of a novel compound, LiFeV 2 O 7 , has been determined from single-crystal X-ray diffraction data. The phase crystallizes in the noncentrosymmetric monoclinic Cc space group. The structure can be described as a layered type compound alternating (Li,Fe)−O sheets and V−O chains that are perpendicular to the [101] direction. Within the (Li,Fe)−O sheets, "hexagonal" holes are formed and assembled into tunnels running parallel to the [201] direction and hosting the vanadium atoms. Original (V 4 O 14 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
(75 reference statements)
3
12
0
Order By: Relevance
“…It can be confused as a polyanionic framework due to the presence of VO 4 ; however, vanadium also participates in the redox process, whereas the polyanions should be electrochemically inert according to the definition of polyanionic structures. In the previous study, it was hypothesized that both V 5+ and Fe 3+ could be electrochemically reduced in the lithiation process. , A similar behavior was observed for the other phases such as LiFeVO 4 , Fe 4 (V 2 O 7 ) 3 , and Fe 2 V 4 O 13 . , Based on 57 Fe Mössbauer spectroscopy and X-ray diffraction results, Denis et al showed that for LiFeVO 4 both Fe 3+ and V 5+ are reducing during the process of lithiation. In the previous study, LiFeV 2 O 7 (LFVO) achieved around 100 mAh/g on the first cycle from 3.50 to 2.35 V, with a retention of 85% of this capacity after 60 cycles .…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…It can be confused as a polyanionic framework due to the presence of VO 4 ; however, vanadium also participates in the redox process, whereas the polyanions should be electrochemically inert according to the definition of polyanionic structures. In the previous study, it was hypothesized that both V 5+ and Fe 3+ could be electrochemically reduced in the lithiation process. , A similar behavior was observed for the other phases such as LiFeVO 4 , Fe 4 (V 2 O 7 ) 3 , and Fe 2 V 4 O 13 . , Based on 57 Fe Mössbauer spectroscopy and X-ray diffraction results, Denis et al showed that for LiFeVO 4 both Fe 3+ and V 5+ are reducing during the process of lithiation. In the previous study, LiFeV 2 O 7 (LFVO) achieved around 100 mAh/g on the first cycle from 3.50 to 2.35 V, with a retention of 85% of this capacity after 60 cycles .…”
Section: Introductionmentioning
confidence: 73%
“…In the previous study, it was hypothesized that both V 5+ and Fe 3+ could be electrochemically reduced in the lithiation process. , A similar behavior was observed for the other phases such as LiFeVO 4 , Fe 4 (V 2 O 7 ) 3 , and Fe 2 V 4 O 13 . , Based on 57 Fe Mössbauer spectroscopy and X-ray diffraction results, Denis et al showed that for LiFeVO 4 both Fe 3+ and V 5+ are reducing during the process of lithiation. In the previous study, LiFeV 2 O 7 (LFVO) achieved around 100 mAh/g on the first cycle from 3.50 to 2.35 V, with a retention of 85% of this capacity after 60 cycles . The promising behavior of this new structure type as a positive electrode encourages us to investigate the Li dynamics of the phase.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations